Dicyanopyrazine photoredox catalysts: Correlation of efficiency with photophysics and electronic structure - Burešová, Zuzana; Gobeze, Habtom B; Grygarová, Monika; Pytela, Oldřich; Klikar, Milan; Obertík, Róbert; Cibulka, Radek; Islam, Tanjila; Schanze, Kirk S.; Bureš, Filip (Elsevier Science Inc., 2024)
Catalytic performance of three structurally-related dicyanopyrazine catalysts has been investigated in three photoredox transformations including deuteration of aldehydes, cross-coupling of iodo-substituted (hetero)aromatic substrates, and alpha-hydrogen abstraction from amines followed by annulation to pyrroloquinoline. Significantly different catalytic activity of the photocatalysts has been explained with the aid of electrochemical, spectroscopic, and quantum-chemical methods. Electrochemical measurements pointed to reversible oneelectron reduction of the photocatalysts affording the corresponding radical anion, and, therefore, dicyanopyrazines are principally well-suited for reductive quenching cycle. Triplet excited state turned out to be a major excited species employed in photoinduced electron transfer. The measured excited state reduction potentials (Ered* = +1.88/+1.43 V) classify the (5-methoxy)thiophene-substituted dicyanopyrazines among the organic photocatalysts with high oxidation power, which is in contrast to N,N-dimethylanilino-substituted photocatalysts. Whereas 5-methoxythiophene photocatalyst forms triplet excited state almost independently on the solvent polarity, transient absorption spectroscopy evidenced the triplet state of N,N-dimethylanilino derivative only in nonpolar media. Moreover, its subsequent reduction to the corresponding radical anion is chemically cumbersome, which contrast to facile one-electron reduction of both cyano groups of photocatalyst bearing weak 5-methoxythiophene donors. The doublet excited radical anion of the latter proved to be very powerful but short-lived reductant with Eox* = -2.84 V. Its reduction power has been demonstrated in a cross-coupling reaction involving consecutive photoinduced electron transfer to preassociated iodo(hetero)arenes. Hence, bis(5methoxythiophen-2-yl)-2,3-dicyanopyrazine can be utilized in photoredox catalysis either as powerful oxidant or reductant.
Dikyanpyrazinové fotoredoxní katalyzátory: korelace účinnosti s fotofyzikou a elektronovou strukturou
Keywords: Dicyanopyrazine; Photoredox catalysis; Deuteration; Cross-coupling; Transient absorption spectra; Dikyanpyrazin; Fotoredoxní katalýza; Deuterace; Cross-coupling